(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
On the basis of numerical modeling of the stress-strain state and geodetic observations over deformations bases and foundations of the test building assessed the effectiveness of selected measures of amplification. Checked the convergence the results of individual monitoring activities. Keywords:reconstruction, monitoring, stress-strain state, the base of foundations, reinforcement, analytical model.